Mycoviruses in Aspergilli: A Comprehensive Review - Kotta-Loizou, Ioly; Coutts, Robert H. A. (Frontiers in Microbiology, 2017)
Fungi, similar to all species, are susceptible to viral infection. Aspergillus is arguably the most well studied fungal genus because of its medical, ecological and economical significance. Mycoviruses were initially detected in Aspergillus species almost 50 years ago and the field continues to be active today with ground-breaking discoveries. The aim of the present review is to cover the scientific progress in all aspects of mycovirology as exemplified by Aspergillus-focused research. Initially an overview of the population studies illustrating the presence of mycoviruses in numerous important Aspergillus species, such as A. niger, A. flavus and A. fumigatus with be presented. Moreover the intricacies of mycovirus transmission, both inter- and intra-species, will be discussed together with the methodologies used to investigate viral dispersion in a laboratory setting. Subsequently, the genomic features of all molecularly characterised mycoviruses to date will be analysed in depth. These include members of established viral families, such as Partitiviridae, Chrysoviridae and Totiviridae, but also more recent, novel discoveries that led to the proposal of new viral families, such as Polymycoviridae, Alternaviridae and, in the context of the present review, Exartaviridae. Finally, the major issue of phenotypic effects of mycoviral infection on the host is addressed, including aflatoxin production in A. flavus, together with growth and virulence in A. fumigatus. Although the molecular mechanisms behind these phenomena are yet to be elucidated, recent studies suggest that by implication, RNA silencing may be involved.